Legal Analysis Of MSMEs Trademark Protection From A Trade Law Perspective: The First To File Principle - Amelia Cendikia Al Khansa; Gaga Alfarghana 'Aisy; Ghefira Nur Fatimah; Gina Sonia; Nabilla Fitri Arfian; Naysila Fitri Solihat; Rizkia Novebiani Putri; Gaga Al Farghana Aisy; Nandang Najmudin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the legal protection of Micro Small and Medium Enterprises trademarks within the Indonesian trademark regime from a trade law perspective by focusing on the application of the first to file principle. The research employs a normative juridical method supported by a descriptive analytical approach and relies exclusively on secondary legal materials, including legislation, judicial decisions, scholarly literature, and relevant legal doctrines. The analysis reveals that the first to file principle provides a structured mechanism for determining trademark ownership and contributes to commercial certainty in trade relations. The study also identifies persistent structural challenges affecting MSMEs, including limited legal awareness, registration barriers, unequal access to legal protection, trademark appropriation practices, and normative gaps concerning prior users. These conditions create tensions between formal legal recognition and substantive economic justice. Through doctrinal and conceptual analysis, the study proposes a reconstructed protection framework that integrates good faith considerations, recognition of prior use, alternative dispute resolution mechanisms, collective trademark models, digital registration reforms, and targeted incentive policies. The findings indicate that a balanced approach between legal certainty and equitable protection is necessary to strengthen MSME competitiveness and support sustainable trade development in Indonesia.